2011
DOI: 10.1051/0004-6361/201116472
|View full text |Cite
|
Sign up to set email alerts
|

Planckearly results. XXIII. The first all-sky survey of Galactic cold clumps

Abstract: We present the statistical properties of the Cold Clump Catalogue of Planck Objects (C3PO), the first all-sky catalogue of cold objects, in terms of their spatial distribution, dust temperature, distance, mass, and morphology. We have combined Planck and IRAS data to extract 10 342 cold sources that stand out against a warmer environment. The sources are distributed over the whole sky, including in the Galactic plane, despite the confusion, and up to high latitudes (>30 • ). We find a strong spatial correlatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(2 citation statements)
references
References 136 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…In particular, the Planck collaboration released a whole sky distribution of dust temperature T d and dust opacity τ 353 at 5 arcmin resolution which was achieved through sensitive measurements of the dust emission above 100 GHz in the Galactic foreground. Five papers by the Planck collaboration presented comparisons between CO and dust emission (Planck Collaboration et al 2011b, 2011c, 2011d. These studies derived basic physical relationships between neutral gas and dust emission and concluded that dark gas (Grenier et al 2005) occupies 15% of the ISM, where the H i emission is assumed to be optically thin.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the Planck collaboration released a whole sky distribution of dust temperature T d and dust opacity τ 353 at 5 arcmin resolution which was achieved through sensitive measurements of the dust emission above 100 GHz in the Galactic foreground. Five papers by the Planck collaboration presented comparisons between CO and dust emission (Planck Collaboration et al 2011b, 2011c, 2011d. These studies derived basic physical relationships between neutral gas and dust emission and concluded that dark gas (Grenier et al 2005) occupies 15% of the ISM, where the H i emission is assumed to be optically thin.…”
Section: Introductionmentioning
confidence: 99%
“…A dispersion of polarization angles is often measured as a standard deviation of the angles assuming that an underlying magnetic field is uniform with a direction equal to the mean orientation of the polarization segments over quite a large area, or the whole area, of a molecular cloud or core (e.g., Kirk et al 2006;Curran & Chrysostomou 2007;Cortes et al 2016;Choudhury et al 2019). Other methods include a nonuniform magnetic field model to fit the overall shape of polarization segments (Girart et al 2009), a two-point correlation function to determine the field structure function (e.g., Hildebrand et al 2009;Houde et al 2009;Poidevin et al 2010;Chuss et al 2019), and a spatial filter to estimate the underlying field morphology (Pillai et al 2015). applied an "unsharp masking" method that uses a moving average of polarization angles with a 36″ × 36″ subregion of Orion A to get the large-scale mean magnetic field.…”
Section: Methods and Resultsmentioning
confidence: 99%